Level of Food Consumption by Population of Sverdlovsk Region (Budget Surveys in 1986—1990) - V. N. Mamyachenkov; E. S. Kulikova; M. I. Lvova (Научный диалог, 2021)
Issues related to the level of consumption by the population of the USSR in the “perestroika” period of its history are considered. In order to conduct an objective historical analysis of the problem, the authors used materials from the funds of three archives, some of which are introduced into scientific circulation for the first time. It is emphasized that the second half of the 1980s was crucial for the Soviet Union, becoming the last five years in its difficult history. The results of a comparative analysis of food consumption by the population of the Sverdlovsk region in the study period are presented. A clear discrepancy between the level of consumption of a number of food products by the population of the Middle Urals and the norms of their scientifically grounded rational consumption is determined. The emphasis is made on the fact that in the diet of Soviet citizens there was always a very shortage of vegetables, melons, fruits and, to some extent, fish products. It is proved that the chronic underconsumption of these products was to a certain extent “compensated” by the increased consumption of sugar, confectionery and dairy products, and in the difficult 1940s–1950s — bakery products and potatoes.  It is concluded that it is not necessary to overly dramatize the “material” factor in the development of disintegration processes that led to the collapse of the Soviet Union.